Modern Railway Services in Africa : Building Traffic - Building Value - World Bank (World Bank, Washington, DC, 2020)
The role of rail in Sub-Saharan Africa (SSA) changed considerably in the latter years of the twentieth century. Although some upgrading has occurred, most SSA networks outside South Africa are still operating to the standards to which they were originally constructed. To encourage the commercialization of the railways and reduce the burden on government finances, several countries concessioned their rail system from the 1990’s on. However, rail infrastructure improvements which encourage modal shift generate benefits from lower road congestion and maintenance costs, fewer road accidents, less pollution, and reduced greenhouse gas emissions. In recent years, many governments in Africa have therefore taken a renewed interest in rehabilitating and upgrading their railways, or in constructing new ones. They desire to improve their logistics efficiency and promote a green mode of transport that is less carbon intensive than road. The railways in Africa can be divided into four broad groups: mineral railways; new railways; legacy railways; and commuter railways. This note reviews the current situation and discusses the challenges and possible approaches to address them.